2022
DOI: 10.1088/1742-6596/2250/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

LTE-based passive forward scattering radar for drone detection and classification

Abstract: Passive forward scattering radar is a system that consists of a transmitter that generates microwaves domain, and at the receiver part, receives LTE-based signal from the transmitter, which will result in the Doppler signature of any object. This system can actually be used for detecting the presence of guided missiles, human, aircraft and drone that pass through between the transmitter and receiver. For this study, the main objective is to detect a drone, which are mainly used by humans to trespass or enter s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…At that point, the ultrasonic range sensor estimates the distance that it takes for an ultrasound wave sent out by the emitter to ricochet off from the object and returns to the receiver with the speed of sound being approximately 341 m/s noticeable in the air [8]. In previous studies on detection of a drone at two different heights from the ground by using passive forward scattering radar have found that lower height indicated greater performance compared to upper height in Principal Component Analysis (PCA) and confusion matrices analysis due to cross sectional area of drone that trespassing the forward scatter region [9]. The main objective of this project is to improve the PFSR system with an ultrasonic range sensor remote measuring device and support by Internet of Things (IoT) using mobile phone applications for security alarm systems in drone detection.…”
mentioning
confidence: 99%
“…At that point, the ultrasonic range sensor estimates the distance that it takes for an ultrasound wave sent out by the emitter to ricochet off from the object and returns to the receiver with the speed of sound being approximately 341 m/s noticeable in the air [8]. In previous studies on detection of a drone at two different heights from the ground by using passive forward scattering radar have found that lower height indicated greater performance compared to upper height in Principal Component Analysis (PCA) and confusion matrices analysis due to cross sectional area of drone that trespassing the forward scatter region [9]. The main objective of this project is to improve the PFSR system with an ultrasonic range sensor remote measuring device and support by Internet of Things (IoT) using mobile phone applications for security alarm systems in drone detection.…”
mentioning
confidence: 99%